2011
DOI: 10.4049/jimmunol.1102243
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Tissue-Retentive Lung Memory CD4 T Cells Mediate Optimal Protection to Respiratory Virus Infection

Abstract: We identify here a new class of lung tissue-resident memory CD4 T cells which exhibit tissue tropism and retention independent of antigen or inflammation. Tissue-resident memory CD4 T cells in the lung did not circulate or emigrate from the lung in parabiosis experiments, were protected from in vivo antibody labeling, and expressed elevated levels CD69 and CD11a compared to circulating memory populations. Importantly, influenza-specific lung-resident memory CD4 T cells served as in situ protectors to respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
703
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(728 citation statements)
references
References 23 publications
19
703
3
3
Order By: Relevance
“…Trm cells can provide much more immediate protection, and various studies have demonstrated that they provide the most effective immune protection to the host 14, 15, 17, 30…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…Trm cells can provide much more immediate protection, and various studies have demonstrated that they provide the most effective immune protection to the host 14, 15, 17, 30…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
“…Tissue resident memory cells are identified as CD69+ cells that remain within peripheral tissues following pathogen clearance 30, 31, 32. CD69 is thought to act as a retention signal as it inhibits the surface expression of the sphingosine‐1‐phosphate (S1P) receptor 1.…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…The effector-memory (TEM) subset (Sallusto et al, 1999) is the predominant subset migrating through multiple tissues (Masopust et al, 2001); however, a significant fraction of TEM phenotype cells persist as non-circulating, tissue-resident subsets (TRM) in multiple sites including lungs, intestines, skin, liver, brain, and other mucosal surfaces (for reviews see (Mueller and Mackay, 2016;Schenkel and Masopust, 2014;Thome and Farber, 2015)). TRM mediate optimal protective responses to site-specific infections through rapid mobilization of immune responses in situ (Schenkel et al, 2014a;Teijaro et al, 2011). Mouse models have also demonstrated the feasibility of targeting TRM in vaccines for generating protective immunity (Shin and Iwasaki, 2012;Zens et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, another distinct subset, tissue-resident memory T cells (T RM ) have been described. T RM have been found in several tissues, including the skin, gut, lung and brain [3][4][5][6]. Once established, T RM are maintained independently of circulating T EM and T CM and their presence correlates with superior protection against local viral challenge [3,5,7].…”
Section: Tissue-resident Memory T Cells (T Rmmentioning
confidence: 99%